2003
DOI: 10.1615/jenvpathtoxoncol.v22.i4.30
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological Effects of Mercury in Skin-Lightening Cream

Abstract: Rose skin-lightening cream with a mercury content of 77,513 +/- 71,063 ppm was selected and applied on mice for a period of 1 month at different intervals. Mercury levels were measured in a total of 58 liver, kidney, and brain tissue samples by atomic absorption spectrophotometer coupled to vapor generator accessory. The mean mercury concentration in the tissues of treated mice was 67,472 +/- 70,181 microg/g in the range of 0.391-288.759 microg/g. Looking at the mercury concentration in the tissue samples with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…The signs of chronic inflammation, bile duct proliferation, portal fibrosis and hepatocytic steatosis were similar to those reported in mercury exposed bottlenose dolphins [10] and Arctic beluga whales [11]. Studies on laboratory rodents support these findings [38]. Furthermore, Dietz et al [23] showed that as much as 94% of the mercury in East Greenland polar bear hair sampled during 1892–2001 was likely of anthropogenic origin.…”
Section: Discussionsupporting
confidence: 65%
“…The signs of chronic inflammation, bile duct proliferation, portal fibrosis and hepatocytic steatosis were similar to those reported in mercury exposed bottlenose dolphins [10] and Arctic beluga whales [11]. Studies on laboratory rodents support these findings [38]. Furthermore, Dietz et al [23] showed that as much as 94% of the mercury in East Greenland polar bear hair sampled during 1892–2001 was likely of anthropogenic origin.…”
Section: Discussionsupporting
confidence: 65%
“…Our previous results showed that histopathological changes were observed in the brain, kidney, and liver tissues of these mice after Fair & Lovely or Rose application suggesting its possible toxicity [56]. Furthermore, the severity of pathological changes increased as the number of applications increased [56,57]. When mercury contents in the ovary compared to other tissues (Fig.…”
Section: Mean Mercury Content (Ng/g) In Ovary Tissuesmentioning
confidence: 75%
“…Mercury contents in ovary was significantly lower than in kidney and liver (for both, P=0) but not different from brain (P=0.455). Though kidney seems to be the primary reservoir of mercury with marked histological changes after repetitive skin-lightening applications of either Fair & Lovely or Rose, less extensive changes were also noted in liver and brain [56,57]. Although no morphorgical study was done on ovary in this study, one would expect that repeated applications of these skin-lightening creams even if they contain mercury less than the FDA permissible limit of 0.1 µg/g, they could be a major factor contributing to reproductive impairment.…”
Section: Mean Mercury Content (Ng/g) In Ovary Tissuesmentioning
confidence: 99%
“…Although banned in many countries, a number of studies showed that a number of marketed lightening products still contain these compounds 12,13 . About 45% of commonly used skin‐lightening creams in Saudi Arabia were shown to contain mercury above the FDA’s acceptable limit of 1ppm 14 …”
Section: Introductionmentioning
confidence: 99%